Pertanggungjawaban Perseroan Perorangan Pasca Pergeseran Paradigma Perseroan Terbatas Sebagai Persekutuan Modal - Dimas Cahya Kusuma (Lex Renaissance, 2022)
This study aims to find out the concept of individual corporate responsibility after the enactment of the Job Creation Law. This is a normative legal research that uses a conceptual and statutory approaches. This research concludes that there is an addition to the concept of a legal entity other than a Limited Liability Company, namely an individual company which can be established only with a single shareholder provided that it fulfills the criteria attached to Small Medium Enterprises (UMK). The response to the paradigm shift from the concept of capital partnership whereby a legal entity can be established by a single shareholder is apparently not something new after seeing article 7 paragraph (5) of the Limited Liability Company Law which explains that a Company can be established only with one shareholder entity, such as State Owned Enterprises (BUMN). Meanwhile, the liability for Individual Companies is limited to the shares or assets they own as long as there are no things that are excluded as stated in Article 153 J paragraph (2) of the Law on Job Creation in the ease of doing business cluster due to amendments to the Law on Limited Liability Companies.Key Words: Job creation; individual company; accountability AbstrakPenelitian ini bertujuan untuk mengetahui konsep pertanggungjawaban Perseroan Perorangan setelah diberlakukannya Undang-undang Cipta Kerja. Penelitian ini merupakan penelitian hukum normatif yang menggunakan pendekatan konseptual dan perundang-undangan. Adapun penelitian ini menyimpulkan bahwa terdapat penambahan dalam konsep badan hukum selain Perseroan Terbatas yaitu Perseroan Perorangan yang dapat didirikan hanya dengan seorang pemilik saham tunggal dengan syarat memenuhi kriteria yang melekat pada Usaha Menengah Kecil (UMK). Tanggapan atas terjadinya pergeseran paradigma dari konsep persekutuan modal dengan dapat didirikanya suatu badan hukum oleh pemilik saham tunggal ternyata bukan suatu hal yang baru setelah melihat pasal 7 ayat (5) Undang-undang Perseroan Terbatas yang menjelaskan bahwa Perseroan dapat didirikan hanya dengan satu entitas pemegang saham seperti Badan Usaha Milik Negara (BUMN). Sedangkan pertanggungjawaban bagi Perseroan Perorangan hanya sebatas saham atau harta kekayaan yang dimilikinya sepanjang tidak terdapat hal-hal yang dikecualikan sebagaimana disebutkan dalam Pasal 153 J ayat (2) Undang-undang tentang Cipta Kerja pada klaster kemudahan berusaha atas perubahan Undang-undang Perseroan Terbatas. Kata-kata Kunci: Cipta kerja; perseroan perorangan; pertanggung jawaban